The storybook of legends - Hale, Shannon (New York ; Boston : Little, Brown and Company, 2013)
At Ever After High, a boarding school for the sons and daughters of famous fairy-tale characters, students Apple White and Raven Queen face the moment when they must choose whether to follow their destinies, or change them.
Keywords: Fairy tales -- Fiction; Characters in literature -- Fiction; Fate and fatalism -- Fiction; Friendship -- Fiction; Boarding schools -- Fiction; Schools -- Fiction